Efficacy of endoscopy in the individual screening program for gastric cancer in Fukuoka city: Comparison with X-ray individual and mass screening programs - KOGA, Yasuhiko; NAKAMURA, Yuichi; TAKEDA, Noriyuki; TANAKA, Keiji; TAKAMIYA, Hiroshi; TAKAYAMA, Takehiko; KAMORI, Mitsuo; KITAGAWA, Shinji; MASUDA, Nobuo; KITANO, Kamesaburo; FUJIMI, Tadashi (Journal of Gastroenterological Mass Survey, 2004)
Since 2000, endoscopic examination has been carried out for the individual screening program for gastric cancer in Fukuoka city. The aim of this study was to evaluate the efficacy of endoscopic screening program in comparison to X-ray based screening programs for gastric cancer. During a period from 2000 to 2002, 67162 subjects who received any of three types of screening program for gastric cancer, that is, endoscopic individual screening (EIS group, n=15774), X-ray individual screening (XIS group, n=23546), or indirect X-ray mass screening (XMS group, n=27842), were comparatively analyzed. Among three groups, no difference was observed in gender, while the number of subjects with 70 years or older was greater in EIS groups than in other two groups. The detection rate of gastric cancer in EIS group (0.51%) was significantly higher than in XIS group (028%) or XMS group (0.14%)(p<0.0001). Positive predictive value in EIS group (9.7%) was also higher than in XIS group (2.8%) or XMS group (1.7%)(p<.0001). The rates of early gastric cancer in EIS, XIS and XMS groups were 77.5%, 64.6% and 56.4%, respectively. The cost for detecting one gastric cancer patient was calculated to be 2,810,000 yen in EIS group, 5,250,000 yen in XIS group, and 4, 020, 000 yen in XMS group. These results indicate that the individual screening using endoscopy is the most useful screening program for detecting gastric cancer.